Creating an optimal motivational team climate to help collegiate athletes thrive during the COVID-19 pandemic - Scott, C. E.; Wineinger, T. O.; Iwasaki, S.; Fry, M. D. (Journal of Sport Psychology in Action, 2021)
College athletes` lives have been upended due to the sudden impact of the COVID-19 pandemic. In spring 2020, athletes lost their competition seasons, face-to-face contact with their coaches and teammates, access to their training facilities and equipment, and faced additional struggles specific to the COVID-19 pandemic (e.g., financial, health concerns). The purpose of this paper is to outline strategies coaches can employ to create a caring and task-involving climate on their teams to help athletes thrive during the COVID-19 pandemic. The strategies came from a research study conducted to assess the responses of coaches and teammates that athletes perceived to be supportive during the COVID-19 pandemic.